COVID-19 vaccination: disease status and outcomes of COVID-19 patients admitted in tertiary care hospital in Raigad District of Maharashtra - Pedhambkar, Ratnaprabha B.; Salgotra, Kuldip R.; Bhusare, Dattatray B. (International Journal Of Community Medicine And Public Health, 2024)
Background: COVID-19 pandemic had witnessed serious infections and deaths during third wave of the pandemic. This study was designed to analyse the association between severity of disease and patient outcomes with vaccination status of COVID-19 patients. Methods: Retrospective record-based study was conducted among 258 COVID-19 patients from August 2021 to January 2022, during the third wave of the pandemic in a tertiary care hospital. Results: Out of the 258 patients, 42% patients were above 60 years of age 19% were in the age group of 18-30 years. 58% male and 42% female patients. Overall, 50% and 36% patients above 40 years had severe and moderate disease respectively. 52% had mild disease in age group of 18-30 years and this was statistically significant with Chi-square value of 38.85 and p<0.05. 36%, 36% and 28% vaccinated patients had severe, moderate and mild disease respectively. 38%, 40% and 23% unvaccinated patients had severe, moderate and mild disease respectively. The mortality rate was 25%, 32% and 50% among vaccinated, unvaccinated and unknown vaccination status respectively. The mortality rate was 44% in those above 60 years. The survival rates were 90% in patients below 40 years. This difference was statistically significant with Chi-square value of 32.16, p<0.005. The mortality rate was 61%, 16% and 2% with severe, moderate and mild disease respectively. Conclusions: The severity and mortality rate was less in vaccinated patients. This shows that vaccination might be effective in reducing the severity of disease and deaths among COVID-19 patients.